AIDS, identity, and community : the HIV epidemic and lesbians and gay men - Greene, Beverly; Herek, Gregory M.; Society for the Psychological Study of Lesbian and Gay Issues (Thousand Oaks, Calif. : Sage Publications, 1995)
Hit hard by the AIDS epidemic in the United States and in much of Europe, the gay and lesbian community has been forced to examine existing notions of what it means to belong to a community based on sexual orientation. The editors of this second volume in the annual series on Psychological Perspectives on Lesbian and Gay Issues have collected a perceptive array of chapters that explore sexual behavior, personal identity, and community memberships of gay men and lesbian women. With the exception of a few, the chapters reflect study findings from AIDS-related research and include discussions of AIDS in large urban centers and in less populated settings outside of major AIDS epicenters. Focusing on underconsidered AIDS populations, the contributors explore specific topics concerning the AIDS epidemic among gay and bisexual men of color, lesbian women, and gay and lesbian youth.
Accessible and sensitive, the book also examines relevant public policy, volunteerism, and long-term survival as important to AIDS awareness and education.
HIV and the gay male community: one clinician's reflections over the years / Neal King -- Lesbians at risk for HIV: the unresolved debate / Cynthia A. Gómez -- HIV/AIDS prevention and the impact of attitudes toward homosexuality and bisexuality / Theo G.M. Sandfort -- Identity and community among gay and bisexual men in the AIDS era: prelimary findings from the Sacramento men's health study / Gregory M. Herek, Eric K. Glunt -- AIDS-related risks and same-sex behaviors among African American men / John L. Peterson -- The Sexual identity and behavior of Perto Rican men who have sex with men / Alex Carballo-Diéguez -- AIDS risk, dual identity, and community response among gay Asian and Pacific Islander men in San Francisco / Kyung-Hee Choi [and others] -- Psychosocial stressors in a panel of New York City gay men during the AIDS epidemic, 1985 to 1991 / Laura Dean -- Coming out as lesbian or gay in the era of AIDS / Mary Jane Rotheram-Borus, Joyce Hunter, Margaret Rosario -- Long-term survival with AIDS and the role of community / Robert H. Remien, Judith G. Rabkin -- AIDS volunteerism: lesbian and gay community-based responses to HIV / Allen M. Omoto, A. Lauren Crain -- The Importance of HIV prevention programming to the lesbian and gay community / William A. Bailey.
"Sponsored by the Society for the Psychological Study of Lesbian and Gay Issues, Division 44 of the American Psychological Association."
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: AIDS (Disease) -- Social aspects; Gay people; AIDS (Disease); Social ecology; Homosexuality; Male homosexuality; Acquired Immunodeficiency Syndrome; Social Environment; Homosexuality; Homosexuality, Male; Sida -- Aspect social; Personnes homosexuelles; Sida; Écologie sociale; Homosexualité.; Homosexualité masculine; male homosexuality; human ecology; homosexuality; HEALTH & FITNESS -- Diseases -- AIDS & HIV; MEDICAL -- AIDS & HIV; Social ecology; Homosexuality; AIDS (Disease); AIDS (Disease) -- Social aspects; Gay people; Homosexualität; Aids; HIV; Homoseksuelen; Sociale identiteit; AIDS -- Sociology